Disentangling carbon stocks and structural characteristics of secondary forests in Tuyen Quang, Vietnam - Nguyen, Minh Canh; Bui, Manh Hung; Khan, Pervez; Park, Junghwan; Nguyen, Thi Bich Phuong; Shiou Yih, Lee; Duan, Jie; Nguyen, Thi Oanh; Pham, The Anh; Vu, Tien Hung; Nguyen, Khac Vinh (Ecological Questions, 2025)
Forest structure is a key to effective forest management. This study analyzed diameter and height data collected from two plots in Tuyen Quang, Vietnam to elucidate the structural characteristics and carbon stocks of the forests. The forest volume varied between 77.59 and 103.93 m³, while the carbon stock ranged from 32.53 to 43.83 (Ton/ha). Additionally, the number of carbon credits spanned from 119.38 to 160.86. The best function for simulating the diameter frequency distribution was Wakeby and Gen. Gamma (4P). Meanwhile, the best function for the height frequency distribution was Dagum and Log-Logistic (3P). The regression between diameter and height was best described by the Power and Naslund equation. A strong association between diameter, height and forest tree quality was revealed in both plots. Good trees were typically clustered within groups with larger diameters and heights, whereas bad trees were predominantly found in the smallest groups. These findings will support the assessment of a forest's ecological functions, contributing to effective carbon sequestration initiatives and climate change mitigation efforts in the future.